Type 2 Diabetes Mellitus Intersects With Pancreatic Cancer Diagnosis and Development - Duan, Xiaoye; Wang, Weihao; Pan, Qi; Guo, Lixin (Frontiers in Oncology, 2021)
The relationship between type 2 diabetes mellitus (T2DM) and pancreatic cancer (PC) is complex. Diabetes is a known risk factor for PC, and new-onset diabetes (NOD) could be an early manifestation of PC that may be facilitate the early diagnosis of PC. Metformin offers a clear benefit of inhibiting PC, whereas insulin therapy may increase the risk of PC development. No evidence has shown that novel hypoglycemic drugs help or prevent PC. In this review, the effects of T2DM on PC development are summarized, and novel strategies for the prevention and treatment of T2DM and PC are discussed.